Great meat : classic techniques and award-winning recipes for selecting, cutting, and cooking beef, lamb, pork, poultry and game /: classic techniques and award-winning recipes for selecting, cutting, and cooking beef, lamb, pork, poultry and game. (2013) - Kelly, Dave; Hogan, John
No abstract available